Measurement of Some Blood Parameters in Smokers of Men in the Province of Al-Muthanna - Areej Shakeer Jassum (Journal of Global Pharma Technology, 2018)
The detached of this study is to consider the influence of smoking on some blood parameters and to calculate the negative special influences of cigarette on the biochemical properties of blood in males. This study was lead at Al- Hussein Educational Hospital in AL- Muthanna province."The study excluded (80) blood samples of men, (40) including smokers and (40) non-smokers and were considered a control group."The age of smokers and control group ranged between (20-50) years .The samples of blood were reserved and the hemoglobin concentration, full number of red blood cells, blood volume and full number of white blood cells were calculated. The results presented a significant enhance (p <0.05) in white blood cells, red blood cells, packed cell volume , grand cell and hemoglobin paralleled with control group. The study also displayed non- significant differences in the total of plates, lymph cell and mid cell paralleled with control group. In deduction, our findings displayed that continuous cigarette smoking has severe adverse influences on blood parameters (such as hemoglobin, total renal corpuscle). "These changes may be linked with a greater risk of developing at hero sclerosis, red fera, chronic uncooperative pulmonary disease or heart disease and blood vessels.